NAGARI FOREST MANAGEMENT AS A MEANS OF FOREST CONFLICT RESOLUTION IN NAGARI SUNGAI BULUAH - Tamrin, Tamrin; Afrizal, Afrizal; Febriamansyah, Rudi; Asrinaldi, Asrinaldi (Jurnal Widya Publika, 2025)
This research starts from the problem of forest management between forest conservation objectives and socio-economic utilization objectives. The ideological conflict between the two approaches can be overcome through management of property rights and access to forest resource utilization. One of these efforts is carried out by the government through the implementation of social forestry policies. Social forestry policy in Indonesia also contains conflicts due to the scope of forests and the historical facts of forest management which are different between Java and outside Java, such as in social forestry management in Nagari Sungai Buluah. Departing from the problems above, this research aims, among others; (1) explain social forestry management as a means of resolving customary forest conflicts; (2) explaining Nagari forest management as a means of improving the social and economic welfare of the community and as a means of nature conservation. This research uses a qualitative method with a case study approach. The research location is the Nagari Sungai Buluah, from the results of the research conducted, it was found that there are subjective and objective conflicts in social forestry management. The nagari expansion policy changes the form of conflict from objective to subjective in the nagari government's relationship with traditional institutions. This research is limited to forms of conflict that occur in official mechanisms in forest management outside Java, it is recommended that research be carried out on social forestry management conflicts on the island of Java.